2006
DOI: 10.1089/ten.2006.12.877
|View full text |Cite
|
Sign up to set email alerts
|

Nucleofection-BasedEx VivoNonviral Gene Delivery to Human Stem Cells as a Platform for Tissue Regeneration

Abstract: There are several gene therapy approaches to tissue regeneration. Although usually efficient, virusbased approaches may elicit an immune response against the viral proteins. An alternative approach, nonviral transfer, is safer, and can be controlled and reproduced. We hypothesized that in vivo bone formation could be achieved using human mesenchymal stem cells (hMSCs) nonvirally transfected with the human bone morphogenetic protein-2 (hBMP-2) or -9 (hBMP-9) gene. Human MSCs were transfected using nucleofection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
123
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 66 publications
7
123
1
1
Order By: Relevance
“…26,27 It was recently shown that the BMP-2, -6, -7 and -9 genes are the most potent inducers of osteogenic differentiation among the BMP family. [28][29][30] In this study we used the BMP-9 gene, since our previous observations indicated it could lead to more significant osteogenesis than the human BMP-2 plasmid. 28 We hypothesized that, in optimized acoustic conditions, the direct in vivo sonoporation of naked DNA encoding an osteogenic gene recombinant human BMP-9 (rhBMP-9) would induce bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 It was recently shown that the BMP-2, -6, -7 and -9 genes are the most potent inducers of osteogenic differentiation among the BMP family. [28][29][30] In this study we used the BMP-9 gene, since our previous observations indicated it could lead to more significant osteogenesis than the human BMP-2 plasmid. 28 We hypothesized that, in optimized acoustic conditions, the direct in vivo sonoporation of naked DNA encoding an osteogenic gene recombinant human BMP-9 (rhBMP-9) would induce bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleofection has been used successfully for transient transfection of human, bovine, rat and porcine MSCs, but has never been tested in BM-derived mMSCs. [34][35][36][37] Magnetically enhanced nucleic acid delivery (magnetofection) has not explored for any type of MSCs to date. We found that nucleofection is a very efficient transfection technique for mMSCs with transfection rates of B60%.…”
Section: Nonviral Gene Transfer Into Murine Mscsmentioning
confidence: 99%
“…This is in line with nucleofection data obtained for human MSCs, where transfection rates ranged from 42 to 88%. 36,38,39 Magnetofection yielded transient transfection rates of 30% in mMSCs, whereas lipofection only reached B20%. Earlier reports on lipofection of human and rat MSCs with Lipofectamine described transfection rates of 2% and 20%, respectively.…”
Section: Nonviral Gene Transfer Into Murine Mscsmentioning
confidence: 99%
“…Nucleofection is a technique whereby the plasmid DNA is transfected directly into the cell nucleus through electrical pulse. Aslan et al 17 showed that human bone morphogenetic protein-2 or 9-nucleofected BM-hMSCs were able to induce bone formation 4 weeks after in vivo engraftment. However, the low level of gene expression signifies the need for long-term selection of stable clones.…”
Section: Introductionmentioning
confidence: 99%